Representasi Konflik Sosial Dalam Kumpulan Cerpen “Robohnya Surau Kami” Karya A.A. Navis: Perspektif Sosiologi Sastra - Wa Mulianti; Nanik Handayani; Aria Bayu Setiaji (Universitas Muhammadiyah Surabaya, 2026)
This study aims to describe the representation of social conflict in the short story collection Robohnya Surau Kami by A.A. Navis through the perspective of sociology of literature. The study employed a qualitative approach using content analysis. The data sources consisted of five purposively selected short stories: Nasihat-Nasihat, Dari Masa ke Masa, Robohnya Surau Kami, Pada Pembotakan Terakhir, and Menanti Kelahiran. Data were collected through reading, note-taking, and identifying excerpts containing social conflicts, then analyzed using Soerjono Soekanto’s social conflict theory. The findings show that personal conflict is the most dominant form of conflict, followed by interclass social conflict and political conflict. Personal conflict is reflected through the characters’ inner struggles, while interclass social conflict illustrates economic inequality and power relations. Political conflict is related to struggles for influence and domination in social life. These findings confirm that literary works function as representations of social reality as well as a medium of social criticism.